Rekayasa Komposit Serat Sabut Kelapa sebagai penguat dan Styrofoam Sebagai Matriks - - Hanif; Sulaiman Thalib; Samsul Rizal (Jurnal Teknik Mesin Unsyiah, 2012)
Coconut fibre which is extracted from outer shell of a coconut is a type of natural fibre used as composite board reinforcement in this research. The fibrebinder used in this research was stryrofoam which is a material from polysterene. This research was aimed at finding out the appropriate composition by weight between coconut fibre and polysterene and to find out the physical, mechanical and morphological characteristics of composite board resulted from the engineering process. The construction of composite board was started by cutting the fibres with the length of ≤ 5 mm, then dyeing them into NaOH for 4 hours. After those process, the fibres were dried and weighted. The Styrofoam was dissolved into silane before it was weighted based on its composition. After the coconut fibre and polysterene mixtures were mixed,they were poured into the composite board mold. The benefit of this composite board is that it is more water resistant. The test results for tensile, density, moisture content, and thickness swelling meet the Indonesian National Standard (SNI) 03-2105-2006. The flexural strength of composite board which meets the standard is the compositions of 30:70, 40:60, and 50:50, while the compositions of 60:60 and 70:30 do not meet the standard.